Bankable Assets : Africa Faces Many Obstacles in Developing Financial Systems - Christensen, Jakob (World Bank, Washington, DC, 2012)
Sound, deep, and efficient financial sectors are vital for high sustained, private sector-led growth. But financial sectors in their current form pose major problems for the economies of sub Saharan Africa (SSA). Insufficient access to credit by small and medium- sized enterprises constrains their ability to expand and limits countries' growth potential. Most households cannot build formal savings, so their ability to escape poverty by investing in education or housing is limited.